Oxytocin alleviates high-fat diet-induced anxiety by decreasing glutamatergic synaptic transmission in the ventral dentate gyrus in adolescent mice - Cao, Xi; Wang, Qiyuan; Zhang, Lina; Sun, Huichao; Xu, Gang; Chen, Xiao; Wu, Zhihong; Liu, Huibao; Yuan, Gaole; Wu, Jian; Liu, Tao (Neuropharmacology, 2025)
A high-fat diet (HFD)-induced obesity is associated with mental disorders in adolescence. However, the mechanisms underlying these associations remain unclear. In this study, we hypothesized that synaptic remodeling occurs in the ventral hippocampus (vHP) of obese mice. To investigate this, we established a postnatal model of HFD-induced obesity in mice and observed increased body weight, elevated plasma luteinizing hormone and testosterone levels, premature puberty, and enhanced anxiety-like behavior in male subjects. We also examined the effect of HFD on the c-Fos protein expression in the ventral dentate gyrus (vDG) and explored the influence of intracerebroventricular (i.c.v) oxytocin injections on HFD-induced anxiety. Our results indicated an increase in c-Fos-positive cells in the vDG following HFD consumption. Additionally, we recorded the spontaneous synaptic activity of miniature excitatory postsynaptic currents (mEPSCs) in the vDG. Notably, HFD resulted in an elevated mEPSC frequency without affecting mEPSC amplitude. Subsequently, investigations demonstrated that i.c.v oxytocin injections reversed anxiety-like behavior induced by HFD. Moreover, the application of oxytocin in a bath solution reduced the mEPSC frequency in the vDG. These findings suggest that postnatal HFD intake induces synaptic dysfunction in the vDG, associated with the hyperactivity of vDG neurons, potentially contributing to the anxiety-like behavior in juvenile obesity. •Postnatal HFD-fed male mice exhibit anxiety-like behavior in adolescence.•HFD induces c-Fos activation in the ventral dentate gyrus.•Intra-ventricular injection of oxytocin alleviates HFD-induced anxiety.•In vitro application of oxytocin reduces miniature EPSC frequency of ventral dentate gyrus granule neurons.